Laterality of sacral stress fractures in trained endurance athletes: Are there biomechanical or orthopaedic risk factors? - Riedl, M.; Roediger, J.; Pohlmann, J.; Hesse, J.; Warschun, F.; Wolfarth, B.; Ueberschär, O. (Sport-Orthopädie - Sport-Traumatologie, 2022)
Background The sacral stress fracture in athletes is still considered an uncommon overuse injury despite a constantly growing number of cases, including the reigning triple Ironman World Champion. Several cases of sacral stress fractures may thus still be missed or misdiagnosed by orthopaedists and (sports) physicians because of insufficient knowledge combined with only unspecific main symptoms. Although the sacrum is thought to be loaded symmetrically during symmetric load-bearing sports like endurance running or triathlon, sacral stress fractures in athletes commonly occur unilaterally instead of bilaterally in the massa lateralis. This study addresses the question whether orthopaedic and/or biomechanical lateralities may contribute to or cause this asymmetric injury localisation.